The deubiquitinating enzyme MINDY2 promotes pancreatic cancer proliferation and metastasis by stabilizing ACTN4 expression and activating the PI3K/AKT/mTOR signaling pathway - Liu, Peng; Liu, Songbai; Zhu, Changhao; Li, Yongning; Li, Ying; Fei, Xiaobin; Hou, Junyi; Wang, Xing; Pan, Yaozhen (Frontiers in Oncology, 2023)
The pathogenic mechanisms of pancreatic cancer (PC) are still not fully understood. Ubiquitination modifications have a crucial role in tumorigenesis and progression. Yet, the role of MINDY2, a member of the motif interacting with Ub-containing novel DUB family (MINDY), as a newly identified deubiquitinating enzyme, in PC is still unclear. In this study, we found that MINDY2 expression is elevated in PC tissue (clinical samples) and was associated with poor prognosis. We also found that MINDY2 is associated with pro-carcinogenic factors such as epithelial-mesenchymal transition (EMT), inflammatory response, and angiogenesis; the ROC curve suggested that MINDY2 has a high diagnostic value in PC. Immunological correlation analysis suggested that MINDY2 is deeply involved in immune cell infiltration in PC and is associated with immune checkpoint-related genes. In vivo and in vitro experiments further suggested that elevated MINDY2 promotes PC proliferation, invasive metastasis, and EMT. Meanwhile, actinin alpha 4 (ACTN4) was identified as a MINDY2-interacting protein by mass spectrometry and other experiments, and ACTN4 protein levels were significantly correlated with MINDY2 expression. The ubiquitination assay confirmed that MINDY2 stabilizes the ACTN4 protein level by deubiquitination. The pro-oncogenic effect of MINDY2 was significantly inhibited by silencing ACTN4. Bioinformatics Analysis and Western blot experiments further confirmed that MINDY2 stabilizes ACTN4 through deubiquitination and thus activates the PI3K/AKT/mTOR signaling pathway. In conclusion, we identified the oncogenic role and mechanism of MINDY2 in PC, suggesting that MINDY2 is a viable candidate gene for PC and may be a therapeutic target and critical prognostic indicator.